2015
DOI: 10.1080/01446193.2015.1042887
|View full text |Cite
|
Sign up to set email alerts
|

Designing robust and revisable policies for gender equality: lessons from the Australian construction industry

Abstract: The construction industry remains the most male dominated sector in Australia. Several decades of formal gender equality initiatives by government and business have failed to bring about any meaningful change to the hierarchical and numerical representation of women in the sector. Drawing on new institutionalism, particularly the concepts of 'robustness' and 'revisability', the nature and intent of formal policies and programs that impact on gender equality are analysed in two large Australian multinational co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 28 publications
(39 reference statements)
2
93
0
Order By: Relevance
“…Sexism and long hours are the key reasons given, a point echoed by Galea, Powell, Loosemore, and Chappell (2015). Clarke et al 's (2005) survey reported employers' organisations as stating lack of facilities for women and working hours that were incompatible with childcare as being major barriers to women's increased participation.…”
Section: Industry Level -The Implementation Of Gender Diversity Initimentioning
confidence: 96%
See 2 more Smart Citations
“…Sexism and long hours are the key reasons given, a point echoed by Galea, Powell, Loosemore, and Chappell (2015). Clarke et al 's (2005) survey reported employers' organisations as stating lack of facilities for women and working hours that were incompatible with childcare as being major barriers to women's increased participation.…”
Section: Industry Level -The Implementation Of Gender Diversity Initimentioning
confidence: 96%
“…Clarke et al 's (2005) survey reported employers' organisations as stating lack of facilities for women and working hours that were incompatible with childcare as being major barriers to women's increased participation. However, as Galea et al (2015) report, work-life balance and flexible working are coming onto the agenda, not as a strategy to address the lack of women in the industry, but to meet demands from men as domestic family roles evolve. Galea et al (2015) also report that while diversity is considered a core principle, it is not prioritised in the same way as safety, as it lacks the 'crisis' drivers of safety breaches, which can prove costly for organisations, financially, reputationally, or for moral and ethical reasons.…”
Section: Industry Level -The Implementation Of Gender Diversity Initimentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, we have witnessed an explosion of quantitative methodologies for analyzing the resilience and robustness of socioeconomic systems [9,10]. However, the literature of policy analysis at the process level is mainly qualitative [11][12][13]. Consequently, the tools and recommendations in this line of research are based solely on case studies and on an informal treatment of complexity.…”
Section: On the Nature Of Resilience And Policy-makingmentioning
confidence: 99%
“…This issue of the poor representation of female in the construction industry is a concern among construction stakeholders. Previous studies posit that issues such as bad company policies with respect to recruitment and promotion, inadequate or unsafe working conditions, the tasks, the number and variability of hours worked, the monotony of the job, time pressures, targets, the consequences of mistakes, and family commitment constitutes some of the intrinsic factors that impose barriers to female under-representation in construction industry (Lingard and Francis, 2002;Loosemore and Waters, 2004;Lingard and Lin, 2004;Galea et al, 2015). The masculine nature of the construction industry, which is mostly characterized by its high levels of conflict and confrontational practices as well as its recruitment practices, has been known for some time to be a source of frustration for its female employees (Gale, 1994;Fielden et al, 2000;Fielden et al, 2001).…”
Section: Introductionmentioning
confidence: 99%